Scientometric analysis of lipid metabolism in breast neoplasm: 2012–2021 - Lin, Xiaobing; Yang, Qiuping; Zheng, Daitian; Tian, Huiting; Chen, Lingzhi; Wu, Jinyao; Ji, Zeqi; Chen, Yexi; Li, Zhiyang (Frontiers in Physiology, 2023)
In recent years, more and more studies have proved that lipid metabolism plays an essential role in breast cancer’s proliferation and metastasisand also has a specific significance in predicting survival. This paper collected data from 725 publications related to lipid metabolism in breast neoplasm from 2012 to 2021 through the Web of Science Core Collection database. Bibliometrix, VOSviewer, and CiteSpace were used for the scientometrics analysis of countries, institutions, journals, authors, keywords, etc. The number of documents published showed an increasing trend, with an average annual growth rate of 14.49%. The USA was the most productive country (n=223, 30.76%). The journals with the largest number of publications are mostly from developed European countries. Except for the retrieved topics, “lipid metabolism” (n=272) and “breast cancer” (n=175), the keywords that appeared most frequently were “expression” (n=151), “fatty-acid synthase” (n=78), “growth” (n=72), “metabolism” (n=67) and “cells” (n=66). These findings and summaries help reveal the current research status and clarify the hot spots in this field.